Scientific behaviour: values and epistemology - doi: 10.4025/actascihumansoc.v33i1.10752 - Jesús Alberto Valero Matas; Juan Romay Coca; Sergio Miranda Castañeda (Acta Scientiarum. Human and Social Sciences, 2011)
Science as a human activity relates to different human values, and therefore it is capable of ethic valuation, both for its consequences as for its process and its action. For this reason, otherwise as the neopositivists and the empirism have suggested, ethics can not be separated from the scientific analysis. The responsibility relationship appears followed by moral responsibility, that places in its actions the exercise of freedom and personal commitment, that without any doubt are basic values in an individual’s behaviour, and, therefore, in a scientist. But these characters are part of any human activity, and they must respond responsibly before the actions derived from it. We are no longer before ethically traditional models, but we move in dynamic ethical planes. The scientific models that currently operate compel scientists to modify that attitude, and consequently, our reflection on this issue ends with a valuation on the need of an ethics of the science, or at least, to put on page the protocols of this issue.